Fluminagrion gen. nov. for Acanthagrion taxaense Santos, 1965, from Brazil (Odonata: Coenagrionidae) - Anjos Santos, Danielle (2013)
A new genus of Coenagrionidae, Fluminagrion, from Rio de Janeiro, Brazil is described, diagnosed, and illustrated, based on examination of the type series and additional specimens of Acanthagrion taxaense Santos, 1965, deposited in the collection of MNRJ/Brazil. This genus is characterized by: posterior lobe of prothorax trilobate, with medial lobe rounded and projected in both sexes; segment 3 of genital ligula C-shaped in lateral view, bifid in ectal view, ending in lobes directed laterally with apexes pyramidal in cross-section; male cercus entire and decumbent from proximal fourth, with brush-like setae at about half its length; female lacking mesepisternal fossa, S8 with vulvar spine.